Analisis Implementasi Multimedia Interaktif pada Aplikasi Duolingo sebagai Media Pembelajaran Bahasa Digital - Cindy Anggriani; Nasrullah Gunawan; Amira Salsabila; Ali Ikhwan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The development of digital technology has driven educational transformation through the use of interactive multimedia as a learning medium. Although the Duolingo application is widely used, most previous studies have focused primarily on testing its effectiveness on user learning outcomes, while specific analyses regarding its interactive feature architecture remain limited. This study aims to analyze the implementation of interactive multimedia features in the Duolingo application as a digital language learning medium. The approach used is descriptive qualitative, utilizing direct observation of the application system without involving user questionnaires. Data analysis was conducted through screenshot evidence reduction, narrative data presentation, and drawing conclusions based on multimedia standard literature. The results indicate that Duolingo has comprehensively implemented text, visual, and audio elements to create two-way communication. Interactivity is strongly built through microphone-based pronunciation evaluation features, instant feedback systems, and an integrated gamification approach. In conclusion, the feature anatomy in Duolingo meets the criteria for responsive and adaptive interactive multimedia, making it highly functional in facilitating users' self-directed learning.